Laser-induced periodic surface structures in solids - Gorbyk, P. P.; Grechko, L. G.; Kunitskaya, L. Yu.; Lerman, L. B.; Semchuk, A. Yu. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2007)
The theory of formation the laser -induced spatial - periodic surface structures in solid state is constructed. The spatial and temporary distribution of temperature on a surface of a solid state which is heated up as a result of interaction a several laser beams (interference patternits surface) with this surface is investigated. The special method of calculation the temperature field, which non-stationary and periodic in space, in a general case is realized. It is shown, that the maximum of heating up is observed at centers of beams and temperature quickly falls down with a movement to edge of a periodic structure. With rather large sections of beams it is possible to reach almost uniform heating up, when the ratio of beam size to a period of structure makes 0,8.